Pengaruh Inflasi dan Nilai Tukar Terhadap Bursa Saham Indonesia - Al Gaza, Muhammad Habib (Universitas Negeri Surabaya, 2023)
This study aims to analyze the effect of inflation and exchange rates on the Indonesian stock market. The data used is annual data from 2018 to 2022. The method used in this research is multiple linear regression analysis. The results of the data analysis show that the inflation variable (X1) partially has no significant effect on the Indonesian stock market with a calculated t value that is smaller than t table and a significance value greater than 0.05. This also happens to the exchange rate variable (X2), which partially has no significant effect on the Indonesian stock market. In addition, the results of data analysis show that the inflation (X1) and exchange rate (X2) variables simultaneously have no significant effect on the Indonesian stock market with a calculated F value that is smaller than F table and a significance value greater than 0.05. This study concludes that inflation and the exchange rate have no significant effect on the Indonesian stock market in the period from 2018 to 2022. However, further research can be conducted using different analytical methods or with more complete data to strengthen the results of this study.